Milk fatty acid composition of dairy goats fed increasing levels of Flemingia macrophylla hay - Oiticica de Carvalho, Isabel das Neves; Moreira da Fonseca, Carlos Elysio; Ferraz Lopes, Fernando Cesar; Frota Morenz, Mirton Jose; Sundfeld da Gama, Marco Antonio; Souza, Vinicius Carneiro de [UNESP]; Silva, Aline Barros da (Univ Estadual Londrina, 2019)
The effect of dietary inclusion of increasing levels of Flemingia macrophylla hay on the yield, composition and fatty acid profile of milk from Saanen x Boer goats was evaluated. The diets were composed of 40% concentrate and 60% forage. The treatments were defined by the level of inclusion of Flemingia hay in the diet (0, 80, 160, 240 and 320 g kg(-1) dry matter) in replacement of the Cynodon dactylon cv. Tifton-85 hay, distributed according to a 5 x 5 Latin Square design. The inclusion of Flemingia in the diet did not change the milk yield or milk fat content but promoted a quadratic effect on the fat yield. A quadratic effect was observed on the milk protein and lactose contents, but this effect was not reflected in the daily production of these components. The concentrations of vaccenic, rumenic, elaidic and trans-10 C18:1 fatty acids in milk fat increased linearly in response to the dietary inclusion of Flemingia, whereas the contents of palmitic, stearic, oleic, linoleic and alpha-linolenic fatty acids were not modified. A linear reduction was observed in the lauric and myristic fatty acids concentrations, which was accompanied by a reduction in the atherogenic index of milk fat. A quadratic effect was also observed on the trans-10, cis-12 CLA milk fat content in response to the inclusion of Flemingia in the diet, as well as a linear increase in the apparent transfer of alpha-linolenic acid from the diet to milk. The inclusion of up to 320 g kg(-1) of Flemingia hay as a replacement for Tifton-85 hay in the Saanen x Boer daily goat diet does not modify the milk production and improves the nutritional quality of milk fat by increasing the contents of rumenic and vaccenic acids beneficial to human health and reducing the concentrations of hypercholesterolemic fatty acids.
Keywords: Conjugated linoleic acid; Fabaceae; Leguminous; Rumenic acid; Vaccenic acid